Isu Rasisme dalam Hubungan Internasional : Narasi “Asian Hate” dan Mispersepsi Amerika Serikat terhadap China di Tengah Pandemi Covid-19 - Ananda Yuan Hasnaa (International Relations, Faculty of Social and Political Sciences, Universitas Diponegoro, 2023)
As a country with the high criminality level in treating the coloures skinned tribes badly, the United States uses the discrimination, as a political method, to blame the society by spreading hatred among them in order to make cracks among them. The discrimantion has always been in line with the white supremacy policy. It started to come up in public again when the virus of Covid-19 orginated from appred in the United States, which the statements “Chinese Virus” and “Kungflu Virus” at the mention of Covid-19 became a factor in the occurrence of the Asian Hate phenomenon. In this study, an analysis will be carried out using the theory of perceptions and misperceptions to find the reasons behind this concern about Asian Hate. This research will answer the question “How Does the Issue of Racism Affect the United States' Perception of Cina in Creating Asian Hatred in the Midst of the Covid-19 Pandemic?”. The purpose of this research is to analyze the country's perceptions that can cause a phenomenon or misperceptions against a competing country using the theory of perceptions and misperceptions by Robert Jervis. This study uses a qualitative research type where the data will be processed using descriptive methods. As a result, Asian Hate is rising as a misperception between United State and China because of white supremacy.